Indirect adaptive model predictive control of wastewater system - Nilchiyan, Mohammad Reza (2010)
Wastewater treatments is the essential part of the environment protection for survive the life of alive objects. The wastewater is used in this position to safe the substrate concentration within the standard limitation and achieved the concentration of dissolved oxygen to a certain values by controlling. Nowadays, there are number of control system design tools available to generate controllers for such systems and models. The values of them, Depends on their accuracy, fast and cost effective method are different. First of all needs to know about the model of the system before any implementation. It is described by a set of nonlinear equations thus we need to have a perfect understanding of how to take a set of nonlinear equations and write down a series of linear equations describing the system. There are several methods to analyze the linearity of the wastewater system. Subspace state space system identification algorithm(N4SID) estimates the state-space by finding its matrices and returns them as an identification system. It is easy and simple to determine the state space system matrices with more mathemathical capability. The wastewater treatment systems are complex, non-linear processes, with multiple inputs and outputs. Designing of active system for indirect adaptive model prediction of waste water is a complex task which involves few stages which includes modelling, simulation and controller parts. When the process parameters are unknown or variable, adaptive controller is a best option to achieve or maintain a desired level of system parameters. Approximate the plant's unknown nonlinear functions and robust control terms are used to make up for approximation errors is aim to design.